Customer Aggression and Organizational Turnover Among Service Employees in Metro Manila, Philippines - Bungato Jr., Guillermo; Nartea, Mecmack; Samonte, Giscellve Iveth (Social Sciences and Development Review, 2023)
The “Customer is always right” has been the motto of many service organizations for the longest time. It mirrors companies’ commitment to do their utmost best in creating a good customer environment to ensure that customers enjoy quality service. But there are instances that customers can get aggressive in social interactions with service employees. These instances do not only affect the marketing and sales aspect of the organization but can ultimately affect the service employees’ output quality and even prompt them to quit. This paper examined how customer aggression affects turnover intentions of service employees. This looked specifically on the effects of customer aggression on the emotional exhaustion, job satisfaction, and turnover intentions of service employees. Survey data was collected using stratified sampling from 328 service employees of KFC branches around Metro Manila. These data were analyzed using the GLM module in Jamovi. Results showed that customer aggression indeed influences emotional exhaustion and in turn decreases job satisfaction and increases turnover intentions. The mitigating effects of distributive justice on the customer aggression-emotional exhaustion relationship was confirmed. However, the mitigating effect of organizational pride on the job satisfaction turnover intentions relationship has been found to be significantly weak. These findings revealed the importance of having policies that communicate equity and justice, as well as the existence of rewards and recognition programs that can boost employee morale and loyalty.